Advancing SDG 4 through Contextual Robotics Learning Devices to Enhance Technical and Problem-Solving Skills in Vocational Education - Muhamad Zuhrie; Agus Wiyono; Fendi Achmad; Dwi Aqidah; Afrizal Luthfi Eka Arnatha; Muhammad Nawwarudin Nawwarudin (Journal of Current Studies in SDGs, 2026)
Objective: To development of a comprehensive robotics learning device package for vocational engineering education based on Contextual Teaching and Learning (CTL) principles. This research contributes to Sustainable Development Goal 4 (SDG 4) by promoting quality education through innovative, contextual, and competency-based learning approaches that support technical skill development and problem-solving abilities. Method: The research employed a Research and Development (R&D) methodology guided by the 4-D model (Define, Design, Develop, Disseminate) and the ADDIE framework. The developed learning package consists of six components: Mechanical Robot Module, Electronics Robot Module, Software Robot Module, Student Worksheets (LKPD), Learning Evaluation Instruments, and Robotics Practicum Guide. Validation was conducted by experts, followed by initial student trials to evaluate feasibility and learning responses. Results:  Expert validation across seven aspects resulted in an average feasibility score of 86.6%, categorized as Very Feasible. Initial student trials demonstrated positive responses, showing improvements in learning engagement, module attractiveness, instructional interactivity, and robotics skills through contextual project-based problem-solving activities. The developed learning package achieved an overall research achievement rate of 90.6%. Novelty: The study provides a novel contribution by integrating CTL principles into a comprehensive robotics learning device package that connects theoretical knowledge with real-world industrial applications. The findings highlight how contextual technology-based learning supports SDG 4 by strengthening quality vocational education, enhancing student competencies, and preparing learners for industry-oriented challenges.